Princeless. Book 4, Be yourself - Whitley, Jeremy (Action Lab Comics, 2015)
Having finished their adventure with The Pirate Princess, Adrienne and Bedelia continue their quest to rescue Adrienne's sisters. Boy-crazy middle sister Angoisse is trapped in a tower deep in the darkest swamp, guarded by zombies, goblins, and the Grimmorax.